Identification of a novel gene signature with regard to ferroptosis, prognosis prediction, and immune microenvironment in osteosarcoma - Zheng, Di; Xia, Kezhou; Wei, Zhun; Wei, Zicheng; Guo, Weichun (Frontiers in Genetics, 2022)
Ferroptosis is a novel form of non-apoptotic cell death that mainly results from the iron-dependent lethal accumulation of lipid peroxidation products. Here, we defined differentially expressed genes between control and RSL3-treated osteosarcoma cells as ferroptosis-associated genes (FAGs) in osteosarcoma. Then, these FAGs were subjected to weighted gene correlation network analysis (WGCNA) and we found that the turquoise module, containing 71 FAGs, was markedly related to patients’ vital status. After that, FAGs in turquoise module were utilized to constructed a prognostic multigene (COL5A2, HOXB4, and UNC5B) signature for risk stratification in the osteosarcoma. Validation in internal and external cohorts indicated the accuracy and clinical applicability of the signature in predicting the prognosis of patients with osteosarcoma. Univariate and multivariate Cox regression analysis suggested that our signature-derived risk score was an independent indicator of patients’ prognosis. Immunological analysis indicated that significant variations in stromal and ESTIMATE scores, as well as tumor purity, were found when high- and low-risk groups were compared. As for the immune cell infiltration, the proportion of activated CD4 memory T cell was significantly decreased in the high-risk group compared with the low-risk group. ssGSEA results suggested that the scores of CD8+ T, Tfh, and Th1 cells were consistently lower in the high-risk group than in the low-risk group. In terms of immune-related activities, the high-risk group had considerably lower scores for inflammation-promoting, T cell co-inhibition, and T cell co-stimulation than the low-risk group, indicating the differential immunological state of high- and low-risk groups. Of the three FAGs comprised in the signature, the expression of COL5A2, HOXB4, and UNC5B were higher in high-risk groups and the expression of COL5A2 and UNC5B were negatively associated with patients’ prognosis. Additionally, the mRNA levels of COL5A2 and HOXB4 were lower and UNC5B mRNA levels were greater in RSL3-treated cells compared with control cells. In all, we systematically analyzed the transcriptional changes of osteosarcoma cells induced by RSL3 and constructed a novel three-gene signature with regard to ferroptosis, prognosis prediction, and immune microenvironment, and we identified COL5A2, HOXB4, and UNC5B as potential therapeutic targets and important regulators of ferroptosis in osteosarcoma.